(3JMQjQ GdeLSWis - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3HWdejhS GdMcjes ((3eQJVi eMeO eDef s)
(3ChdgG (B:s
(3GdMeO ddg eHOC cd eHOC , hZGjI cd ZGjI hHYO , abO cfJ HQgI ef GdReGf , YGRekG Ydi Cf CMQQ dfaSi , hdSGFQ WdHg GdYde ef GdENhGf , cJGH GdeLSWi , GdefShH Edi HWdjehS GdbdhPi s
(3BNQgG (B:s
(3aEPG CJeefG LeY eG jZfi GdLGO SDGd ef hLhO eG jMJGL Edjg Edi hLhOg , hJUMjM eG jMJGL Edi JUMjMg adfNJe GdcJGH , hCbhd hEPG habfi Gddg JYGdi GGjVkG Ydi JeGe eG aUdJg hEfLGR eG hYOJg Je GdcJGH s
(3fSNI KGfjIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ ai HYV GdCdaGXs
(3cJHJ Hbde eged GdfbW CMjGfkG HgG cKjQ ef GdLOGhd hGdQShe GdgfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs